(untitled) (World of finance, 2020)
Introduction. In the context of reforming the system of local self-government and territorial organization of power, they need to rethink a number of important theoretical postulates of domestic financial science through the prism of improving existing and developing new conceptual approaches to the theoretical substantiation of the finances of the united territorial communities in their territorial communities. After all, the study of OTG finances, with their permanent dominance in local finance, is the basis for effective implementation of the reform of financial decentralization and local development. Moreover, upon completion of the reform, the UGT finances will prevail, completely changing the local finances. Purpose. Given the limited theoretical and practical experience of domestic scientists on the finances of the united territorial communities, the purpose of the article is to find out the place and role of OGF finances in the financial system of the state. Methods. The methods of abstraction, generalization, induction, deduction, synthesis were applied in the study of the role and place of OGF finances in the financial system of the state, as well as the system method. Results. The views of domestic and foreign theorists and practitioners on the scientific substantiation of the financial system of the state and its structural components have been systematized. The LTG finances in its structure and the role for modifications of local finances was determined. This made it possible to identify OTG finances as an area of the financial system and to formulate a science-based approach to their knowledge, while separating OTG budgets, utility and financial institutions and local borrowing in their structure. Discussion. It is advisable to carry out further scientific researches of OGF finances on the basis of the formed theoretical substantiation of OGF finances as an integral part of the financial system of the state with the corresponding structural structure – links that are interconnected and interact.